2013
DOI: 10.3402/tellusb.v65i0.20174
|View full text |Cite
|
Sign up to set email alerts
|

Meteoric CaO and carbon smoke particles collected in the upper stratosphere from an unanticipated source

Abstract: Nanometre CaO and pure carbon smoke particles were collected at 38-km altitude in the upper stratosphere in\ud the Arctic during June 2008 using DUSTER (Dust in the Upper Stratosphere Tracking Experiment and\ud Retrieval). This balloon-borne instrument was designed for non-destructive collection of solid particles\ud between 200 nm to 40 mm. We report here on micrometre CaCO3 (calcite) grains with evidence of thermal\ud erosion and smoke particles that formed after melting and vaporisation and complete dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…It is possible, however, that a much larger cometary bolide, containing both nanometre and micrometre-sized biological entities (viruses and bacteria), disintegrated in the upper stratosphere and recondensed into the amorphous DNA imbued structures shown in Figures 1-3. This could well be similar to the reconstitution of calcite and carbon dust from the material of an exploding meteorite described by Corte et al [14].…”
Section: Membrane Stainingsupporting
confidence: 86%
“…It is possible, however, that a much larger cometary bolide, containing both nanometre and micrometre-sized biological entities (viruses and bacteria), disintegrated in the upper stratosphere and recondensed into the amorphous DNA imbued structures shown in Figures 1-3. This could well be similar to the reconstitution of calcite and carbon dust from the material of an exploding meteorite described by Corte et al [14].…”
Section: Membrane Stainingsupporting
confidence: 86%
“…4.1 Origin of the observed particle types 4.1.1 Ca-rich particles Ca-rich particles in the upper stratosphere were recently described by Della Corte et al (2013). These authors specify Ca-C-F particles, calcite / aragonite particles and a porous aggregate of Ca(O) nanograins, sampled at 38 km height.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, several previous publications which describe the presence of a variety of other refractory particle groups in addition to carbonaceous particles. These additional particle groups include metallic particles (Chuan and Woods, 1984;Sheridan et al, 1994;Chen et al, 1998;Baumgardner et al, 2004;Ebert et al, 2016), meteoritic particles (Murphy et al, 1998(Murphy et al, , 2007Renard et al, 2008, silicates (Testa et al, 1990;Ebert et al, 2016), crustal-type particles (Sheridan et al, 1994;Chen et al, 1998), and Ca-bearing particles (Della Corte et al, 2013;Ebert et al, 2016).…”
Section: Occurrence Of Refractory Carbonaceous Particles In the Stratmentioning
confidence: 99%
“…Carbonaceous aerosol was found to contribute to the aerosol population at all latitudes in the stratosphere and interplanetary dust was significantly abundant above 30 km for particles ≥ 0.35 µm (Renard et al, 2008). Della Corte et al (2013) found calcium-oxygen (CaO)-rich particles probably originating from a bolide that penetrated the Earth's atmosphere. Single-particle mass spectrometry (SPMS) brought new insights into the chemistry of stratospheric particles (e.g., Murphy et al, 1998Murphy et al, , 2007Murphy et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%